Early versus late parenteral nutrition in term and late preterm infants: a randomised controlled trial - Karen Simmer; Sanjay Patole; Shripada Rao; Trevor A Mori; Elizabeth McKinnon; Kwi Moon; Kevin Croft (BMJ Publishing Group, 2024)
Background There is limited evidence regarding the optimal time to commence parenteral nutrition (PN) in term and late preterm infants.Design Single-centre, non-blinded, exploratory randomised controlled trial.Setting A level-3 neonatal unit in a stand-alone paediatric hospital.Patients Infants born ≥34 weeks of gestation and ≤28 days, who needed PN. Eligible infants were randomised on day 1 or day 2 of admission.Interventions Early (day 1 or day 2 of admission, N=30) or late (day 6 of admission, N=30) PN.Main outcome measures Plasma phenylalanine and F2-isoprostane levels on day 4 and day 8 of admission. Secondary outcomes were amino-acid and fatty-acid profiles on day 4 and day 8, and clinical outcomes.Results The postnatal age at randomisation was similar between the groups (2.3 (SD 0.8) vs 2.3 (0.7) days, p=0.90). On day 4, phenylalanine levels in early-PN infants were higher than in late-PN (mean (SD) 62.9 (26.7) vs 45.5 (15.3) µmol/L; baseline-adjusted percentage difference 25.8% (95% CI 11.6% to 39.9%), p<0.001). There was no significant difference in phenylalanine levels between the two groups on day 8. There was no significant difference between the groups for F2-isoprostane levels on day 4 (early-PN mean (SD) 389 (176) vs late-PN 419 (291) pg/mL; baseline-adjusted percentage difference: −4.4% (95% CI −21.5% to 12.8%) p=0.62) and day 8 (mean (SD) 305 (125) vs 354 (113) pg/mL; adjusted mean percentage difference −16.1 (95% CI −34.1 to 1.9) p=0.09).Postnatal growth restriction for weight was less severe in the early-PN group (change in weight z-score from baseline to discharge: −0.6 (0.6) vs −1.0 (0.6); p=0.02). The incidence of hyperglycaemia was greater in the early-PN group (20/30 (66.7%) vs 11/30 (36.7%), p=0.02).Conclusions The timing of the commencement of PN did not seem to affect the degree of oxidative stress in critically ill term and late preterm infants. The effect of transiently high plasma phenylalanine with early PN on clinical outcomes requires further investigation.Trial registration number ACTRN12620000324910.